2013
DOI: 10.1002/mrd.22285
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines in ovarian folliculogenesis, oocyte maturation and luteinisation

Abstract: SUMMARYCytokines are key regulators of ovarian physiology, particularly in relation to folliculogenesis and ovulation, where they contribute to creating an environment supporting follicle selection and growth. Their manifold functions include regulating cellular proliferation/differentiation, follicular survival/atresia, and oocyte maturation. Several cytokines, such as TGF-b-superfamily members, are involved at all stages of folliculogenesis while the production of others is stage-dependent. This review draws… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
125
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(137 citation statements)
references
References 449 publications
(492 reference statements)
1
125
0
11
Order By: Relevance
“…Numerous studies have confirmed that inflammatory cytokines play an important regulatory role in ovarian activity [38-40]. In particular, the discovery and application of specific inhibitors and gene knockout animals have more substantiated the previous speculation about the involvement of inflammatory cytokines in follicular development and ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that inflammatory cytokines play an important regulatory role in ovarian activity [38-40]. In particular, the discovery and application of specific inhibitors and gene knockout animals have more substantiated the previous speculation about the involvement of inflammatory cytokines in follicular development and ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Women with PCOS are typically characterized by a large number of oocytes collected during IVF, they are frequently of poor quality, leading to decreased fertilization, cleavage and implantation rates, and poor pregnancy outcome (Gardner et al, 2018). The relationship between the immunological pro ile of the FF and oocyte developmental potential and implantation outcome has been uncovered (Field et al, 2014). To improve the assisted conception outcome, one essential problem that needs to be uncovered is to precisely predict oocyte and embryo developmental potential.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing number of the proin lammatory cytokines were found in the peripheral circulation and follicular luid of retrieved oocytes obtained during IVF cycle of PCOS women (Qiao and Feng, 2011;Duleba and Dokras, 2012;Repaci et al, 2011). Cytokines have been found to be directly related to maintaining the delicate balance of the hypothalamic-pituitary-ovarian axis and involved in the maintenance of normal ovarian and menstrual cycles (Field et al, 2014;Trunov et al, 2016). Cytokines are considered the key to reproductive success, creating an immune permissive, embryo receptive environment supporting gametogenesis, fertilization, early development of the embryo, implantation of the blastocyst, and the fetus growth (Cb et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Those oocytes and their surrounding follicle cells are referred to as primordial follicles (20)(21)(22). Before birth, a small portion of primordial follicles begin to develop multiple layers of follicle cells (granulosa cells) surrounding the growing oocyte.…”
Section: Oocyte Maturationmentioning
confidence: 99%